Efficient multiparty quantum key agreement with collective detection. Issue 1 (December 2017) - Huang, Wei; Su, Qi; Liu, Bin; He, Yuan-Hang; Fan, Fan; Xu, Bing-Jie
Abstract As a burgeoning branch of quantum cryptography, quantum key agreement is a kind of key establishing processes where the security and fairness of the established common key should be guaranteed simultaneously. However, the difficulty on designing a qualified quantum key agreement protocol increases significantly with the increase of the number of the involved participants. Thus far, only few of the existing multiparty quantum key agreement (MQKA) protocols can really achieve security and fairness. Nevertheless, these qualified MQKA protocols are either too inefficient or too impractical. In this paper, an MQKA protocol is proposed with single photons in travelling mode. Since only one eavesdropping detection is needed in the proposed protocol, the qubit efficiency and measurement efficiency of it are higher than those of the existing ones in theory. Compared with the protocols which make use of the entangled states or multi-particle measurements, the proposed protocol is more feasible with the current technologies. Security and fairness analysis shows that the proposed protocol is not only immune to the attacks from external eavesdroppers, but also free from the attacks from internal betrayers.